Influence of manganese doping to the full tensor properties of 0.24Pb(In(1/2)Nb(1/2))O(3)-0.47Pb(Mg(1/3)Nb(2/3))O(3)-0.29PbTiO(3) single crystals - Sun, Enwei (American Institute of Physics, 2013)
Complete sets of elastic, piezoelectric, dielectric, and electromechanical properties of [001](c) and [011](c) poled pure and 0.5 wt. % manganese-doped 0.24Pb(In(1/2)Nb(1/2))O(3)-0.47Pb(Mg(1/3)Nb(2/3))O(3)-0.29PbTiO(3) single crystals have been characterized at room temperature. The results indicate that manganese ion substitution in the B-site of perovskite 0.24PIN-0.47PMN-0.29PT single crystals makes the material harder with much higher mechanical quality factor Q(m) and slight decrease in piezoelectric and dielectric constants. The much improved Q(m) value (200–900) makes Mn-doped single crystals more suitable for high-power transducer applications than pure single crystals.